English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

13 answers

2x-3y=12
+3y +3y Add three to get a zero on on side, but what you do to one side you have to do to the other.
(2x)/2 = (3y +12)/2 (divide by two, to get x by itself)

x= (3y+12)/2

Now substitute
2([3y+12]/2) -3y =12 Now solve for y. Once you get you y answer substitute that back into the original equation to find x. And you'll have x and y

2007-01-07 03:12:28 · answer #1 · answered by Anonymous · 0 0

using algebra,

X = (12 + 3Y) /2
Y = (12 -2X) / -3

HOWEVER

this is not a solution. this is manipulation. you have 1 equation with 2 unknowns (X and Y). when trying to solve a problem, the number of equations MUST equal the number of unknowns. X depends upon Y and Y depends upon X. without more than one equation, there is no solution. this is called logic.

2007-01-07 11:24:53 · answer #2 · answered by michaell 6 · 0 0

You can't solve for one exact number because there are many solutions, but if you knew that y or x equals (let's say 1) then it would be possible.

If not then

2x-3y=12
2x=3y+12
2x=3(y+4)
x=(3[y+4])/2

and

2x-3y=12
-3y=-2x+12
3y=2(x+6)
y=(2[x+6])/3

2007-01-07 11:19:26 · answer #3 · answered by dude guy 2 · 0 0

In order to solve for x and y and obtain a numerical result you need 2 equations. For "n" number of unknowns you need the same "n" number of equations. If you just need to solve for X, then that is the equation of a straight line:

y= 2/3x - 4 For x=0 y=-4 For y=0 x=6

2007-01-07 11:14:36 · answer #4 · answered by Andres C 2 · 0 0

x = 12, y = 4

2(12) - 3(4) = 12

24 - 12 = 12

You need to use systems of equations to solve a problem like this, which would require more equations. Two variables require two equations to solve algebraically.

2007-01-07 11:14:50 · answer #5 · answered by saphie 1 · 0 0

to solve for x, add-3y to both sides then divide each side by 2. so 2x=12+3y then x=6+(3/2)y. to solve for y, subtract 2x from each side then divide each side by -3. so -3y=12-2x then y=-4+(2/3)y

2007-01-07 11:07:15 · answer #6 · answered by clock 2 · 0 1

X = (12 + 3Y) /2

Y = (12 -2X) / -3

2007-01-07 11:05:39 · answer #7 · answered by cato___ 7 · 0 1

There are numerous solutions to this equation. Without more information, it is impossible to find one absolute solution.

2007-01-07 11:16:22 · answer #8 · answered by David K 1 · 0 0

Y equals something that depends on x, and x equals something depending on y. You can't solve it any better than what I just gave you, unless you have a system of equations which you don't appear to have...

2007-01-07 11:07:01 · answer #9 · answered by John R 4 · 0 1

-4+2/3=y
x=6+3/2y

2007-01-07 11:07:16 · answer #10 · answered by me 4 · 1 1

fedest.com, questions and answers